SIMPLIFIED METHODS AND STEPS OF STILL LIFE WORK IN FINE ARTS CLASSES OF HIGHER EDUCATION COUNTRIES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In this article, still life in the lessons of fine arts simplified methods and stages of operation are highlighted. Also, the topic of still life plays an important role in the teaching of fine Arts, because through still life you are also creative through different types of this genre, scientifically based that both solve educational tasks